Mechanistic study of NO oxidation on Cr-phthalocyanine: theoretical insight - Anchalee Junkaew (2018)
© The Royal Society of Chemistry. The reaction mechanisms of NO oxidation on chromium-phthalocyanine (CrPc) were elucidated using density functional theory calculations and compared with NO reduction. The results reveal that the reaction of NO oxidation on CrPc is a two-consecutive step pathway which produces NO2as a product. The first step can proceed through competitive Langmuir-Hinshelwood (LH) and Eley-Rideal (ER) mechanisms presenting the low activation barriers (Ea) in a range of 0.1 to 0.5 eV with exothermic aspects. Moreover, the ER mechanism is found to be more feasible. In the second step, the reaction requires an Eaof 0.32 eV, which is considered as the rate determining step of the overall reaction. By comparing both NO oxidation and reduction, the results reveal that in the low O2system, CrPc converts NO to N2via a dimer (NO)2mechanism whereas in the excess O2system, it oxidizes NO to NO2easily. Both reaction systems required very low Eavalues, thus this low cost CrPc catalyst could be a candidate for NO treatment at room temperature.